1999
DOI: 10.1109/8.761077
|View full text |Cite
|
Sign up to set email alerts
|

A combined field approach to scattering from infinite elliptical cylinders using the method of ordered multiple interactions

Abstract: The method of ordered multiple interactions (MOMI) is an iterative procedure which has been demonstrated to provide a rapidly convergent series for the problem of wave scattering from perfectly conducting surfaces rough in a single dimension. In this paper, we consider the extension of this technique to the problem of scattering from infinite elliptical cylinders. For an incident plane wave having its electric field polarized along the axis of the cylinder a combined field formulation of the scattering problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Chou and Johnson combined FBM with electric field integral equation (EFIE).Furthermore they proposed an acceleration algorithm based on the spectral representation of Green's function which reduces the operational count to O(N ) for PEC surfaces [6], [7]. A combined field approach for scattering from infinite elliptical cylinders using MOMI was presented in [24].…”
Section: And Brown and Called The Methods Of Orderedmentioning
confidence: 99%
“…Chou and Johnson combined FBM with electric field integral equation (EFIE).Furthermore they proposed an acceleration algorithm based on the spectral representation of Green's function which reduces the operational count to O(N ) for PEC surfaces [6], [7]. A combined field approach for scattering from infinite elliptical cylinders using MOMI was presented in [24].…”
Section: And Brown and Called The Methods Of Orderedmentioning
confidence: 99%
“…This treatment is chosen to simplify the analysis of the coupling and it is in harmony with experiments where the half power bandwidth of a laser spike is much smaller than the spacing of the lasing wavelengths. 3,4 Although the electromagnetic fields in an elliptical dielectric waveguide can be studied from numerical method or dyadic Green's function method, [17][18][19][20][21][22] we found that it straightforward to formulate the coupling coefficient by following Yeh's analytical approach. 23 Using Yeh's notation, it is shown in Secs.…”
Section: ͑1͒mentioning
confidence: 99%
“…If both two parts are only singlevalue function of abscissa x rather then multi-value function of x, for example, a conducting Six-Side Polygon Object (SSPO) (see Region 2 and 3 in Fig. 1), the aforementioned FBM(/SAA) [1][2][3][4][5][6][7][8][9][10][11][12] can't be simple used to solve the kind of composite rough surface problem, although the FBM (or equivalent MOMI) can be used to calculate scattering from closed contour of conducting object, for examples, 2-dimensional infinite elliptical cylinders ( [24] and [25]). So the FBM/SAA need be further developed by introduced new calculation technique to solve this kind of inhomogeneous composite rough surface problem.…”
Section: Introductionmentioning
confidence: 99%